1998
DOI: 10.1159/000030215
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Partial Ureteric Obstruction in Newborn Rats

Abstract: Partial obstruction of the left ureter was created in newborn rats. Unobstruction was performed after 2 or 7 days. The investigations were carried out at 9 weeks of age – under slight hydropenia to institute an element of stress. Unobstruction was successful. On the unobstructed side, there were nevertheless impairments as compared to controls: urine osmolality (–32%), free water reabsorption (–44%), potassium excretion (–34%), renal blood flow (–36%) and glomerular filtration (–36%). On the intact contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Harrison et al noted that early functional recovery was inversely proportional to the duration of the obstruction in the fetal lamb model, while Chevalier and colleagues came to a similar conclusion based on work in mice (44, 45). Others, however, have found that histological and functional renal damage may persist despite relief of obstruction, even when conducted during early stages of urinary tract development (46,47).…”
Section: Consequences Of Urinary Tract Obstructionmentioning
confidence: 99%
“…Harrison et al noted that early functional recovery was inversely proportional to the duration of the obstruction in the fetal lamb model, while Chevalier and colleagues came to a similar conclusion based on work in mice (44, 45). Others, however, have found that histological and functional renal damage may persist despite relief of obstruction, even when conducted during early stages of urinary tract development (46,47).…”
Section: Consequences Of Urinary Tract Obstructionmentioning
confidence: 99%